Strategies For Enhancing Financial Literacy And Attitude In Optimizing Poultry Farmers' Business Capital In Boyolali Regency - Nuryanto, Aan; Sidiq, Ahmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research seeks to examine the impact of financial literacy, financial attitude, and financial behavior on the efficiency of business capital management among poultry farmers in Boyolali Regency. The study involved a sample of 100 poultry farmers, chosen through a purposive sampling method. Data collection was conducted using questionnaires and analyzed through multiple linear regression.” “The findings reveal that financial literacy (X1) significantly affects the effectiveness of business capital management, as indicated by a t-value of 8.018 and a p-value below 0.05. Similarly, financial attitude (X2) also has a notable impact, with a t-value of 3.234 and a p-value under 0.05. Conversely, financial behavior (X3) does not exhibit a significant effect on business capital management effectiveness, with a t-value of 1.228 and a p-value exceeding 0.05. The F-test results demonstrate that all three independent variables collectively have a significant impact on business capital management effectiveness, with an F-value of 121.273 and a p-value below 0.05. Furthermore, the coefficient of determination (R²) of 79.1% suggests that financial literacy, financial attitude, and financial behavior account for 79.1% of the variance in business capital management effectiveness, while the remaining portion is influenced by external factors beyond this study.” The findings of this study emphasize the need to strengthen financial education among poultry farmers to support the long-term sustainability of their businesses. It is anticipated that the government and financial institutions will design financial literacy training programs and implement more effective capital management strategies tailored to the poultry farming industry.